Formulating Diets for Improved Health Status of Pigs: Current Knowledge and Perspectives - Lucas A. Rodrigues; Bonjin Koo; Martin Nyachoti; Daniel A. Columbus (Animals, 2022)
Our understanding of nutrition has been evolving to support both performance and immune status of pigs, particularly in disease-challenged animals which experience repartitioning of nutrients from growth towards the immune response. In this sense, it is critical to understand how stress may impact nutrient metabolism and the effects of nutritional interventions able to modulate organ (e.g., gastrointestinal tract) functionality and health. This will be pivotal in the development of effective diet formulation strategies in the context of improved animal performance and health. Therefore, this review will address qualitative and quantitative effects of immune system stimulation on voluntary feed intake and growth performance measurements in pigs. Due to the known repartitioning of nutrients, the effects of stimulating the immune system on nutrient requirements, stratified according to different challenge models, will be explored. Finally, different nutritional strategies (i.e., low protein, amino acid-supplemented diets; functional amino acid supplementation; dietary fiber level and source; diet complexity; organic acids; plant secondary metabolites) will be presented and discussed in the context of their possible role in enhancing the immune response and animal performance.